The development of platinum alloys for jewellery applications by considering both the conventional and the advanced manufacturing techniques-review paper - Lekganyane Kedibone; Khodja-Moller Malika; Mkhonto Donald; Mostert Roelof; Phasha Maje (MATEC Web of Conferences)
The thermophysical properties of platinum (Pt) and its alloys are key when deciding on jewellery fabrication or manufacturing techniques. They include the platinum alloys’ density, viscosity, melting point, thermal conductivity, reflectivity and surface tension as they directly impact traditional manufacturing practices compared to gold (Au) and silver (Ag). This review aims to assess the thermophysical properties of Pt and its alloys by considering their castability, printability and resulting physical and mechanical properties during jewellery platinum alloy development. The alloying elements of interest include copper (Cu), iron (Fe), germanium (Ge), tungsten (W), manganese (Mn), vanadium (V), ruthenium (Ru), rhodium (Rh), iridium (Ir), tantalum (Ta), and titanium (Ti) and their influence on the Pt properties will also be evaluated. The review attempts to define which Pt alloys should perform best, particularly concerning the production methods such as the investment casting technique and 3D metal printing i.e. additive manufacturing technique typical of Laser Beam Powder Bed Fusion (LB-PBF).